ANALISIS KEPUASAN KERJA KARYAWAN DIVISI SDM PT PUSRI (PERSERO) PALEMBANG - MUHAMMAD KOSASIH ZEN; AFRIYADI CAHYADI (JEMBATAN, 2013)
ABSTRACT The purpose of this research is to investigate the influence of motivation, compensation, leadership, organizationa culture, and organizational environment focusing to job satisfaction on individual responses. This apaer uses a quantitative analysis by distributing questionnaires randomly to sixty two respondents as samples. They work for human resource department in PT. Pupuk Sriwidjaja. Findings suggest that the quantitative research approach is useful in showing the influence. Validity and reliability test are used to determine the accuracy of the questionnaires previous to exploring the causal relationship among the variables. The paper call for further research concerning other variables related to job satisfaction.